Profile of pneumocystis infection in a tertiary care institute in North India - Kaur, Ravinder (Indian J Sex Transm Dis AIDS, 2016)
CONTEXT: Pneumocystis jirovecii pneumonia (PcP) is still remains a common opportunistic disease in human immunodeficiency virus (HIV) infected individuals. Study on PcP in developing countries are scarce. AIMS: To study the occurrence of P. jirovecii infection in clinically suspected individuals in a tertiary care institute. SETTINGS AND DESIGN: Retrospective study conducted in a tertiary care hospital. MATERIALS AND METHODS: Two years data regarding respiratory sample analysis, HIV status, and cluster of differentiation 4 (CD4) cell count of clinically suspected pneumocystis infection patients with known/unknown HIV status were analyzed. RESULTS: Data of 45 eligible patients were analyzed. The majority of the patients were male (between 21 and 50 years of age). Total 26 (57.7%) patients were HIV reactive, of which 14 had CD4 count of <200 cells/mm(3). 20 patients (9 HIV reactive and 11 unknown HIV status) were confirmed with pneumocystosis by direct fluorescent antibody (DFA) staining. Four of 14 HIV reactive individuals who had CD4 count of <200 cells/mm(3) and 5 of 12 HIV reactive individuals who had CD4 count of >200 cells/mm(3) were positive for pneumocystosis. CONCLUSIONS: Pneumocystis pneumonia is still prevalent in North India and is mainly affecting patients in economically productive and sexually active age group. To diagnose pneumocystosis, DFA is an easily available method in resource-limited settings. Appreciating the actual HIV or immunodeficiency status and the CD4 profile of an individual with symptoms of pneumocystis infection will help the clinicians in early diagnosis and initiation appropriate therapy in individuals living with the disease.